Primary School Playground and Pupils Physical Skill Acquisition - Hafees Tosin Sulyman; Akinola Sgun Olaosebikan; Jawad Olayemi Olosunde; Ebenezer Oladipupo Oladoye (Indonesian Journal of Sport Management, 2022)
Primary school playground and pupils’ physical skill acquisition is a crucial issue that needs urgent attention because empirical studies have shown that primary school playground can go a long way in influencing pupils’ holistic development and pupils’ physical skill acquisition need to be fully involve in the educational setting. The instrument used was checklist titled primary school playground, material, qualities and activities (PSPMQA); another instrument used was rating scales named pupils physical skill acquisition (RSPA); T-test was used to determine the reliability and index obtained from the instrument were 0.75. The findings revealed that the Primary school playgrounds in Ilorin West Local Government Area, Kwara State have enough space for children to play, it is free from dangerous object, it is safe and secure and also it has grasses. Activities that are always done on playground includes running, hide and seek, passing of ball and kicking of ball. Available playground materials are swings, play sand and natural grass. The level of pupils’ physical acquisition is low (weighted mean= 1.57), Primary school playground qualities have significant influence on pupils’ physical skill acquisition (F (1,375) = .719, P < 0.05), Primary school playground activities have significant influence on pupils’ physical skill acquisition (F (1, 375) = 0.11, P < 0.05), There was no significant difference in pupils’ skill acquisition in Ilorin west Local Government Area, Kwara State based on gender (t = -2.698; df = 374; P > 0.05), The finding revealed that there was no significant difference in pupils’ skill acquisition in Ilorin west Local Government Area, Kwara State school type (t = -2.444; df = 374; P > 0.05). Teacher should allow the pupils to make use of playground to develop their holistic development. It was recommended that the ministries and other concerned agencies should set workshop, seminar and conference on the important of playground on physical skill acquisition on the development of the pupils’.